Cytoprotective Peptides from Blue Mussel Protein Hydrolysates: Identification and Mechanism Investigation in Human Umbilical Vein Endothelial Cells Injury - Indyaswan Tegar Suryaningtyas (MDPI AG, 2021)
Cardiovascular disease represents a leading cause of mortality and is often characterized by the emergence of endothelial dysfunction (ED), a physiologic condition that takes place in the early progress of atherosclerosis. In this study, two cytoprotective peptides derived from blue mussel chymotrypsin hydrolysates with the sequence of EPTF and FTVN were purified and identified. Molecular mechanisms underlying the cytoprotective effects against oxidative stress which lead to human umbilical vein endothelial cells (HUVEC) injury were investigated. The results showed that pretreatment of EPTF, FTVN and their combination (1:1) in 0.1 mg/mL significantly reduced HUVEC death due to H2O2 exposure. The cytoprotective mechanism of these peptides involves an improvement in the cellular antioxidant defense system, as indicated by the suppression of the intracellular ROS generation through upregulation of the cytoprotective enzyme heme oxygenase-1. In addition, H2O2 exposure triggers HUVEC damage through the apoptosis process, as evidenced by increased cytochrome C release, Bax protein expression, and the elevated amount of activated caspase-3, however in HUVEC pretreated with peptides and their combination, the presence of those apoptotic stimuli was significantly decreased. Each peptide showed similar cytoprotective effect but no synergistic effect. Taken together, these peptides may be especially important in protecting against oxidative stress-mediated ED.